Dynamic thermal behavior of micro heat pipe array-air cooling battery thermal management system based on thermal network model. (5th November 2019) - Dan, Dan; Yao, Chengning; Zhang, Yangjun; Zhang, Hu; Zeng, Zezhi; Xu, Xiaoming
Highlights: A micro heat pipe array-air cooling battery thermal management system is proposed. An equivalent thermal resistance model is developed for MHPA based on thermal circuit method. Accuracy of the thermal circuit model is verified by experiments; The cooling effect of the system is compared with air cooling under different operating conditions. Abstract: An effective battery thermal management system is crucial for electric vehicles because the performance of lithium ion battery is sensitive to its operating temperature. In this study, a thermal management system equipped with micro heat pipe array (MHPA) is designed. An equivalent thermal resistance model is developed for MHPA based on thermal circuit method. The accuracy of the proposed model is validated by comparing the simulation results with experimental data under steady and dynamic and operating condition. A validated lumped thermoelectric model is adopted for prismatic lithium ion battery. The proposed thermal resistance model is combined with the battery model in order to predict the transient temperature distribution of a battery pack based on MHPA cooling. Simulations are conducted for air-cooled MHPA thermal management system. Temperature rise and temperature gradients of the designed cooling system are compared with direct forced convection. Simulation results demonstrate that the MHPA-based battery thermal management provides a quick response to ensure the temperature stability during rapid changing operating condition.